Paganismo contemporâneo no Brasil: a magia da realidade. - Bezerra, Karina Oliveira (2019)
Paganism is a contemporary religious movement, which believes in many gods, nature being sacred and worshiped in seasonal rites, with adaptations to life in modern society. The inspiration and reconstruction of the old pre-Christian European religions and / or the indigenous traditions of the country and origin of the practitioners is sought. Our work sought to understand how the reality in Paganism is. So we come to the thesis that Pagan reality is magical. Unlike the magic-religion-science triad, we created the concept of triple magic to represent pagan reality. It is divided into ritual magic, symbolic magic and participatory magic. And such a system of thought can be called magism. We have discovered that magic is the founding link, and agglutinator of Paganism. And that, therefore, magic in Paganism is a resource, rather than a dump. And the various responses given by our 40 interviewees revealed to us that it is the myth that plays the role of belief, and distinguishes Pagan religions. To reach these conclusions we have come a long way. We use Paul Veyne's concepts of "truth programs" and "constitutive imagination." We investigate religion as everyday life with Graham Harvey, and we use Ian Jamison's bodily ethics, in conjunction with Hanegraaff, Pasi, Thomas, and Mauss's magical studies. So we were applying in the: investigation of the origin of formation of Paganism in the romantic movement, which was nostalgic of a past gone (Pagan), seeking an organic union between people, culture and nature; and the new form of magic that comes with secularization, which seeks a mystical union with the divine, combined with the spirit of optimism and faith in human progress and perfection. Having understood this world context that includes the myth and the contemporary Pagan rite, we went to Brazil. We investigated eight Pagan religions: Wicca, Druidism and recon, Heathenism, Hellenism, Shamanism, Goddess Spirituality, Witchcraft and Piaganism. We did: field research in almost all regions of the country, with the exception of the North, visiting eight states, bibliographical research, documentaries and interviews, of which four were face-to-face and 36 were open questionnaires with 31 questions. The interviewees are from all regions of the country, distributed in 15 states. Prioritized people with more time of practice, and with a significant character in the development, dissemination and actuation of contemporary Paganism in Brazil. All the data made it possible to see magic as Whitehead's “process”. It is the imagination, the enchantment, the magic that makes real life, which makes belief in a set of myths a great number of strangers, which enables the practice of a set of gestures to create a reality, and insert their practitioners in a community, perpetuated by the same process of experiencing the subjects.